2018
DOI: 10.17305/bjbms.2018.2400
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine reduces ventilator-induced lung injury (VILI) by inhibiting Toll-like receptor 4 (TLR4)/nuclear factor (NF)-κB signaling pathway

Abstract: Mechanical ventilation (MV) may lead to ventilator-induced lung injury (VILI). Previous research has shown that dexmedetomidine attenuates pulmonary inflammation caused by MV, but the underlying mechanisms remain unclear. Our study aims to test whether dexmedetomidine has a protective effect against VILI and to explore the possible molecular mechanisms using the rat model. Thirty adult male Wistar rats weighing 200-250 g were randomly assigned to 5 groups (n = 6): control, low tidal volume MV (LMV), high tidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Meanwhile, LPS significantly increased the production of TNF-α, IL-6, IL-1β, IL-2, IL-12 and MCP-1 in BV2 cells. Chen et al found that Dex reduces lung injury via inhibiting NF-κB signaling pathway, which was consistent with our results 41. These data indicated that Dex could decrease neuroinflammation in LPS-stimulated BV2 cells via inhibiting NF-κB.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, LPS significantly increased the production of TNF-α, IL-6, IL-1β, IL-2, IL-12 and MCP-1 in BV2 cells. Chen et al found that Dex reduces lung injury via inhibiting NF-κB signaling pathway, which was consistent with our results 41. These data indicated that Dex could decrease neuroinflammation in LPS-stimulated BV2 cells via inhibiting NF-κB.…”
Section: Discussionsupporting
confidence: 93%
“…MV is a life-saving therapy for ardS and patients with acute respiratory failure, such as acute lung injury, and is critical in general anesthesia (12). However, excessive ventilation can exacerbate pre-existing lung damage and damage healthy lungs, this process is known as Vili (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also reported the anti-inflammatory effects of Dex by reducing the expression of inflammatory factors in certain specific cases (27)(28)(29). Considering previous literature reports and clinical dose analysis (11,12), two doses of dex were examined in the present study. The data showed that high doses of Dex at 10 µg/kg/h significantly decreased expression of the inflammation-related cytokines IL-1β, il-6 and TnF-α, W/d ratios and pathological changes in the Vili model rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have veri ed that DEX attenuates ischemiareperfusion injury and lipopolysaccharide and ventilator-induced lung injury. [10][11][12][13] However, the speci c mechanism remains unknown. According to a recent report, α 2 -adrenergic stimulation suppresses oxidative damage and alters the mitochondrial membrane potential (MMP), 14 suggesting that dexmedetomidine, a speci c α 2 -adrenoreceptor agonist, probably exerted a protective effect by in uencing mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%